Limx→1(2x−3)(x−1)2×2+x−3=

Limx1(2x3)(x1)2x2+x3=

  1. A

    110

  2. B

    -110

  3. C

    25

  4. D

    -25

    Fill Out the Form for Expert Academic Guidance!l



    +91



    Live ClassesBooksTest SeriesSelf Learning



    Verify OTP Code (required)

    I agree to the terms and conditions and privacy policy.

    Solution:

    limx1(2x-3)x-12x2+x-3=limx1(2x-3)(x-1)2x2+3x-2x-3=limx1(2x-3)(x-1)x(2x+3)-1(2x+3)=limx1(2x-3)(x-1)(2x+3)(x-1) =limx1(2x-3)(2x+3)(x+1)       since x-1 =x+1 (x-1)=-1(5)(2)

    =110

    Chat on WhatsApp Call Infinity Learn

      Talk to our academic expert!



      +91


      Live ClassesBooksTest SeriesSelf Learning




      Verify OTP Code (required)

      I agree to the terms and conditions and privacy policy.